A Literature Approach: Dynamics of Strategic Management in Increasing the Effectiveness of Public Service - Erlina Setiawati; Herna Fita Fitriana; Ayatulloh; B.I Maliki (Cendekia: Jurnal Pendidikan dan Pembelajaran)
Abstrak